(untitled) (Research, Society and Development, 2021)
Moral-uncertainty-distress (MUD) is defined as moral distress related to conflict about best course of action in morally complex situations. We aim to correlate physician’s perception about advance directives (AD) with MUD, identifying the impact it promotes on clinical decision making. In this a qualitative study, were semi-structured interviews with eight physicians of a hospital in Curitiba-PR, then submitted to analysis content technique by Bardin. The first category identified, AD as a morally challenging element, revealed paternalistic attitudes by some participants, as also insecurities in uncertain prognoses, uncertainty about patient motivations to write the document and little previous knowledge about AD by them. The recognition of AD as instruments that exercises patient’s autonomy was the second category. Although AD were comprehended as instruments of autonomy, other elements were morally challenging, which can be a source of MUD to physician and impact decision making process.